PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS WIZER. ME PADA MATERI RAGAM HIAS SUMATERA UTARA DI KELAS V SD NEGERI 104241 KELURAHAN KAMPUNG SYAHMAD - Cucu Tri Ayu Ningrum; Putra Afriadi; Robenhart Tamba; Winara; Try wahyu Purnomo (STKIP Subang, 2026)
This study aimed to develop a Wizer.me-based Student Worksheet (LKPD) on the topic of North Sumatra Traditional Ornament for fifth-grade students at SD Negeri 104241 Kelurahan Kampung Syahmad and to determine its validity, practicality, and effectiveness. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, documentation, validation questionnaires, practicality questionnaires, and learning outcome tests. The results showed that the developed Wizer.me-based LKPD met the criteria of being highly valid, highly practical, and highly effective. The media expert validation obtained a score of 96%, the material expert validation obtained 92%, and the assessment rubric validation obtained 93.75%, all of which were categorized as highly valid. The teacher practicality test obtained a score of 92.7%, indicating that the LKPD was highly practical, while the effectiveness test showed an N-Gain score of 0.80 (80%), which falls into the high category. Therefore, the developed Wizer.me-based LKPD is considered valid, practical, and effective for use as instructional material in teaching North Sumatra Traditional Ornament to fifth-grade elementary school students.